Utilization of fermented water hyacinth (Eichhornia crassipes) meal in the diets on growth of jelawat (Leptobarbus hoeveni) - Cahyadi, Riatman; Suharman, Indra; ', Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this research was to know the amount of fermented waterhyacinth meal in diets on growth and feed efficiency of Leptobarbus heovenijuveniles. Five isonitrogenous (30% crude protein) experimental diets wasformulated to contain 0, 10, 20, 30, and 40% fermented water hyacinth meal and100, 90, 80,70,and 60% soybean meal (P0, P1, P2, P3, and P4, respectively).Completely randomized design (CRD) was used in this experiment.The result showed that a diet containing 40% fermented water hyacinth mealand 60% soybean meal (P4) support a good specific growth rate (2.18%/day), feedefficiency (29.83%) and protein retention (11.99%). It this concluded that up to 60%soybean meal can be substituted with fermented water hyacinth meal in the diets forLeptobarbus hoeveni juveniles.Key word : diets, growth, fermented water hyacinth, Leptobarbus hoeveni, utilization